Pharmaceutical Product Development Exploiting 3D Printing Technology: Conventional to Novel Drug Delivery System - Alam, Md. S.; Akhtar, Ayesha; Ahsan, Iftikhar; Shafiq-un-Nabi, Sheikh (Current Pharmaceutical Design, 2018)
Background: 3D printed pharmaceutical products are revolutionizing the pharmaceutical industry as a prospective mean to achieve a personalized method of treatments acquired to the specially designed need of each patient. It will depend upon age, weight, concomitants, pharmacogenetics and pharmacokinetic profile of the patient and thus transforming the current pharmaceutical market as a potential alternative to conventional medicine. 3D printing technology is getting more consideration in new medicine formulation development as a modern and better alternative to control many challenges associated with conventional medicinal products. There are many advantages of 3D printed medicines which create tremendous opportunities for improving the acceptance, accuracy and effectiveness of these medicines. In 2015, United State Food and Drug Administration has approved the first 3D printed tablet (Spritam®) and had shown the emerging importance of this technology. Methods: This review article summarizes as how in-depth knowledge of drugs and their manufacturing processes can assist to manage different strategies for various 3D printing methods. The principal goal of this review is to provide a brief introduction about the present techniques employed in tech -medicine evolution from conventional to a novel drug delivery system. Results: It is evidenced that through its unparalleled advantages of high-throughput, versatility, automation, precise spatial control and fabrication of hierarchical structures, the implementation of 3D printing for the expansion and delivery of controlled drugs acts as a pivotal role. Conclusion: 3D printing technology has an extraordinary ability to provide elasticity in the manufacturing and designing of composite products that can be utilized in programmable and personalized medicine. Personalized medicine helps in improving drug safety and minimizes side effects such as toxicity to individual human being which is associated with unsuitable drug dose.
Keywords: hydrogel